Prevalence and determinants of reproductive health services utilisation among childbearing women in Nigeria: Do occupational status and health insurance coverage count? - Chukwuechefulam K. Imo; Chinegbonkpa H. Nwakanma (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Maternal healthcare is vital for women of reproductive age, but underutilisation contributes to poor health outcomes. Nigeria’s maternal mortality remains high despite efforts to strengthen reproductive health services. There is a paucity of empirical evidence on how occupational engagement and health insurance enrolment shape health service utilization in Nigeria. This study analysed pooled data from 49,415 women in the 2018–2024 Nigeria Demographic and Health Surveys to investigate the influence of occupational status and health insurance on reproductive health service utilisation. Findings showed employed women, particularly professionals, demonstrated better healthcare-seeking behaviours. Health insurance coverage increased the odds of attending ≥8 antenatal care visits (aOR: 1.49, CI: 1.24–1.79) and using skilled delivery assistance (aOR: 1.56, CI: 1.19–2.05), but reduced postnatal health check (aOR: 0.78). Pragmatic policies promoting women’s employment, economic empowerment, and universal health insurance are needed to improve outcomes and meet Sustainable Development Goal 3 targets in Nigeria.